Regulation of Eicosanoid Pathways by MicroRNAs - Saul, Meike J.; Emmerich, Anne C.; Steinhilber, Dieter; Suess, Beatrix (Frontiers in Pharmacology, 2019)
Over the last years, many microRNAs (miRNAs) have been identified which regulate the formation of bioactive lipid mediators such as prostanoids and leukotrienes. Many of these miRNAs are involved in complex regulatory circuits necessary for the fine-tuning of biological functions including inflammatory processes or cell growth. A better understanding of these networks will contribute to the development of novel therapeutic strategies for the treatment of inflammatory diseases and cancer. In this review, we provide an overview of the current knowledge of miRNA regulation in eicosanoid pathways with special focus on novel miRNA functions and regulatory circuits of leukotriene and prostaglandin biosynthesis.